Pengembangan LKPD berbasis Tradisi Sambatan pada pembelajaran Bahasa Indonesia Kelas V SD - Dinina, Faza Achsana; Istiq’faroh, Nurul; Putri, Naura Suci Amalia (Innovations in Multidisciplinary Education Journal, 2026)
This research is motivated by the low ability of fifth-grade elementary school students in writing observation report texts and the limited availability of teaching materials relevant to the students' environment. The primary objective of this study is to develop a Student Worksheet (LKPD) based on the local wisdom of the Sambatan tradition and to test its validity and practicality in Indonesian language learning. The method employed is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included validation sheets from material and media experts, as well as teacher and student response questionnaires, which were then analyzed descriptively. The results indicated that the Sambatan tradition-based LKPD was declared valid with an average percentage of 69.4%. The practicality level of the product fell into the highly practical category, with a student response score of 85.3% and a teacher response score of 95.0%. The research findings reveal that the integration of local content is effective in reducing students' cognitive load and increasing learning motivation through contextual materials. The study concludes that this LKPD is feasible for use as both a cultural literacy tool and a functional academic instrument. The implications of this research suggest the importance of intensive guidance during the initial stages of adapting cultural-based scientific report formats to optimize student understanding.